The Dutch canon debate. Reflections of an American - Kennedy, J.C. (BMGN - Low Countries Historical Review, 2006)
James C. Kennedy, The Dutch Canon Debate: Reflections of an American This article offers an overview of the American debate over the ‘History Standards’ in the mid-1990s as a spring board for reflection on current Dutch efforts to develop a historical ‘canon.’ For several reasons, various Dutch attempts at canon-building are more solidly traditionalist than is the case in the United States. This stems in part from the fact that for along time there has been an American ‘canon’ about which to argue, making the past contested ground. Perhaps the greatest advantage of having a ‘canon’ in the Netherlands is to stimulate Dutch historians to offer opposing interpretations of the national past. This article is part of the forum 'Debat over de zin of onzin van een nationale canon'.